2022
DOI: 10.1186/s12885-022-10414-9
|View full text |Cite
|
Sign up to set email alerts
|

SCARA5 induced ferroptosis to effect ESCC proliferation and metastasis by combining with Ferritin light chain

Abstract: Background Esophageal squamous cell carcinoma (ESCC) remains one of the most lethal cancers worldwide accompany with an extremely poor prognosis. Therefore, this study aims to screen for new molecules affecting ESCC and explore their mechanisms of action to provide ideas for targeted therapies for ESCC. Methods Firstly, we screened out the membrane protein SCARA5 by high-throughput sequencing of the ESCC patient tissues, and RT-qPCR and WB were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The typical morphological changes of ferroptosis includes a decrease in mitochondrial volume and mitochondrial cristae, and an increase in mitochondrial membrane density. 48 Moreover, ferroptosis can be regulated by ACSL4 and GPX4. ACSL4 is an enzyme that facilitates free polyunsaturated fatty acids (PUFAs) to synthesize PUFA-phosphatidylethanolamines, which are unstable and prone to LPO.…”
Section: Discussionmentioning
confidence: 99%
“…The typical morphological changes of ferroptosis includes a decrease in mitochondrial volume and mitochondrial cristae, and an increase in mitochondrial membrane density. 48 Moreover, ferroptosis can be regulated by ACSL4 and GPX4. ACSL4 is an enzyme that facilitates free polyunsaturated fatty acids (PUFAs) to synthesize PUFA-phosphatidylethanolamines, which are unstable and prone to LPO.…”
Section: Discussionmentioning
confidence: 99%
“…92 Studies have shown that scavenger receptor protein 5 (SCARA5), located on chromosome 8p21, can increase intracellular ROS and Fe 2+ accumulation by binding to the light chain of ferritin, thus inducing ferroptosis and inhibiting the proliferation and metastasis of esophageal squamous cell carcinoma cells. 93 These recent research advances highlight the clinical therapeutic potential of ferroptosis in CVDs and potential therapeutic strategies.…”
Section: Application Of Ferroptosis In the Treatment Of Cvdsmentioning
confidence: 99%
“…It’s interesting to note that ferroptosis has two sides in tumor growth, necessitating careful target selection. Recently, it was found that DNAJB6 ( 186 ) and SCARA5 ( 187 ) can promote the process of ferroptosis in tumor cells and inhibit tumor progression.…”
Section: Advances In the Treatment Of Esophageal Cancer Metastasesmentioning
confidence: 99%